Menghidupkan Nilai-Nilai Islami Berbasis Awesome Muharram Fest di TPQ Al Ittihad Desa Kertomulyo - Mutista Hafshah; Supitayanti Supitayanti; Eka Intansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to revive Islamic values through the Awesome Muharram Fest activity at the Al-Quran Education Park (TPQ) Al Ittihad, Kertomulyo Village. Awesome Muharram Fest is an educational and recreative program designed to welcome the Islamic new year, as well as a means of learning and strengthening Islamic religious values for children. This activity involved various competitions, namely, there was a calligraphy coloring competition, a daily prayer memorization competition, an adhan competition, a short letters memorization competition, and a gharib competition, with the aim of deepening the understanding of TPQ Al-Ittihad students. In its implementation, ustadz and ustadzah also participated in supporting and assisting the committee in preparing for the competition. The Muharram Fest held by the KKN team went well and smoothly. It is hoped that this competition can be a means of learning and self-development for TPQ Al-Ittihad students of Kertomulyo Village and encourage their enthusiasm for learning and confidence. For the KKN Team, it is hoped that they can take lessons and experiences from various shortcomings that exist during the process of organizing the Awesome Muharram Fest by the KKN Posko 95 group.